THE COMMUNICATION AND INFORMATION TECHNOLOGIES AND WOMEN: CAN THE NEW TECHNOLOGIES DISRUPT THE GENDER? - Nelly P. Stromquist (Ediciones Universidad de Salamanca, 2009)
The ICT has become a referent that has changed the World in which we are living. Globalization, the big flow of people, from South to North, the flexibility provided by the technologies, which allows a quick and fast communication, all of them are elements that characterizes our World. In this article we present some thoughts about the role played by ICTs in the social change during the last decades. We analyze several social movements and their impact on the democratic participation. We also explore the new possibilities open to women in this new context, and we present some options of development that could help them to overcome exclusion.